A study on awareness regarding disposal of unused medicines among consumers at a tertiary care teaching hospital of North India - Gupta, Rohini; Gupta, Brij Mohan; Gupta, Apeksha (International Journal of Advances in Medicine, 2019)
Background: In the recent years, large number of human pharmaceuticals have been introduced to the environment by landfill when household medications are thrown to trash and liquid medications gain access to the environment via liquid drainage systems. There is lack of knowledge and awareness in the general public regarding the safe disposal of unused and expired medicines. The objective was to assess the awareness regarding disposal of unused medicines among consumers at a tertiary care teaching hospital of north India Methods: It was a cross-sectional observational questionnaire-based study carried out on 220 consumers in medicine outpatient department (OPD) of a tertiary care teaching hospital in North India for 3 months. All the participants were provided the pre-validated self-administered questionnaire. The final questionnaire consisted of twelve questions to assess participants’ knowledge and attitude towards disposal of the medicines. The data was analyzed with the help of descriptive statistics. Results: It is quite evident from the present study that majority of participants 56.36% stated 1-5 drugs were left-over drugs at their homes. Most of the leftover medicines were analgesics in 59.1% followed by antibiotics in 51.36%. Most common dosage form of these leftover medicines were tablets in 85.9% of respondents. Majority of the respondents (55.9%) were not aware of the adverse outcomes of the pharmaceuticals in the environment. The most common method followed by majority of the participants for disposing of the solid, semi-solid and liquid dosage forms was garbage in 95%, 91.4% and 76.4% of consumers respectively. About 9.31% of the participants were in favour of initiating a program to collect unused medications from home. Conclusions: It can be concluded from the present study that the consumers had poor knowledge regarding the safe drug disposal techniques. Therefore, efforts need to be done by the health care professionals to make people educate regarding the safe drug disposal techniques.